Robust and blind video watermarking against online sharing platforms - Yajing Fu; Xiaoping Liang; Fengli Lu; Jiayan Wang; Zhenjun Tang (Scientific Reports)
Abstract In recent years, with the access of high-speed broadband, the number of videos on online sharing platforms has increased sharply, and the copyright protection of videos has been widely concerned. However, existing block-based watermarking methods have high sensitivity under geometric deformation and cannot accurately locate the watermark position, which leads to the failure of watermark extraction. Therefore, a robust and blind video watermarking scheme to resist the online sharing platform is proposed. Firstly, DTCWT is used to preprocess the video to reduce the influence of non-geometric signals on the extracted watermark. Secondly, the low frequency domain is divided into rings of different sizes, and the spatial stability region is established to ensure the synchronization of watermark extraction. Finally, the energy of the ring subband is obtained by DCT on the ring, and the watermark embedding is optimized by adjusting the energy relationship of adjacent energy rings to balance the invisibility and robustness of the watermark using the strong correlation of adjacent video frames. The experimental results show that the proposed watermarking scheme can not only resist common video processing operations, but also show good robustness to video online sharing platforms.